Estudio avifaunístico en la parroquia pucayacu, cantón La maná, provincia Cotopaxi - Zurita Moscoso, Angel Israel (2016)
This research is focused on the bird fauna at Pucayacu parish, Canton La Maná, Cotopaxi Province in order to make known the diversity of bird species that it is possible to found in this area. Pucayacu is not categorized as an important ecotouristic or bird watching destination. Or at least the communities of the surroundings have not seen benefits either environmental, economic nor socials. With the previous considerations this project considered strategic places through methodology that allowed to determine the bird richness on those strategic points. By identifiying the ecological niches through the location of natural areas like rivers, fruit trees and affected areas by human actions it was possible to categorize the areas where the probabilities to observe and register birds. The aim of this birds inventory has given a guide with which it is possible to find new ways to promote bird watching as a touristic activity. It might help to open new markets by showing the importance of birds as well as to present it as an attraction of the parish as a promissory activity to help to sustainable development.